The Relevance of the Merdeka Curriculum in Strengthening Students' Character at SDN Pangeran 1 Banjarmasin - Muhammad Tata Andriawan; Mulpina Mulpina; Noor Widad Aulia Rizky; Zahratul Aulia; Hana Aisyah Khumairo; Aslamiah Aslamiah; Diani Ayu Pratiwi (Jurnal Pendidikan Rafflesia, 2026)
This study aims to describe the implementation of the Merdeka Curriculum in strengthening 21st-century skills and the Pancasila Student Profile at SDN Pangeran 1. The study employed a qualitative approach using a case study method. The research participants consisted of the principal, teachers, and students. Data were collected through observations, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Merdeka Curriculum has supported the development of 21st-century skills, including critical thinking, creativity, communication, and collaboration. In addition, the implementation of the Pancasila Student Profile Strengthening Project (P5) has contributed to the development of students' character in accordance with the dimensions of the Pancasila Student Profile. However, several challenges remain, including limited facilities and infrastructure as well as differences in students' characteristics. Therefore, collaboration among schools, teachers, and other relevant stakeholders is essential to optimize the implementation of the Merdeka Curriculum in supporting 21st-century learning.